The ‘Burgundian’ hat from Herjolfsnes, Greenland: new discoveries, new dates - Smith, Michèle Hayeur; Arneborg, Jette; Smith, Kevin P. (Danish Journal of Archaeology, 2015)
In 1921, during Poul Nørlund’s excavation at the Norse farm Herjolfsnes, Greenland, a tall hat was recovered from the burial grounds surrounding the farm’s church, where a substantial collection of medieval garments had been recovered. This unusual hat came to symbolize not only the end of the Greenland Norse colony but also its enduring cultural links with continental European fashions, following a comment to this effect published by Nørlund himself. In 1996, the hat was dated to the early fourteenth century by Arneborg, a century earlier than Nørlund’s dating, based on stylistic comparisons with European examples. Recent research on North Atlantic textiles led to a reexamination of the hat, with different sections sampled and resubmitted for accelerated mass spectrometry dating. The results suggest that the body of the hat and its crown are of different periods with c. 100 years between them. This reanalysis of the Herjolfsnes ‘tall brimless hat’ or ‘Burgundian’ hat suggests that a considerable amount of cloth recycling took place in these North Atlantic colonies, that cloth was a valued and cherished commodity, and raises questions about the role this item of material culture role should play in discussions of identity and enduring links between Greenland and the continent.